Carbon quantum dots: an emerging material for optoelectronic applications. Issue 23 (29th May 2019) - Yuan, Ting; Meng, Ting; He, Ping; Shi, YuXin; Li, Yunchao; Li, Xiaohong; Fan, Louzhen; Yang, Shihe
Abstract : An overview of the synthesis, optical properties, luminescence mechanism, and optoelectronic applications of CQDs is presented. Abstract : As an emerging class of luminescent nanomaterials, carbon quantum dots (CQDs) have recently shown enormous potential for optoelectronic applications on account of their characteristic broad emission, tunable fluorescence emission, high thermal stability, and low cytotoxicity. In this review, we will update the latest research progress achieved in CQDs, including their synthesis, optical properties, luminescence mechanism, and applications in optoelectronics. Mainly reviewed here are their room temperature phosphorescence, delayed fluorescence properties, as well as their optoelectronic applications including light-emitting diodes, lasing, solar cells, and photodetectors. Finally, current problems and challenges of CQD-based optoelectronics applications are discussed with an eye on future development. We hope that this review will provide critical insights to inspire new exciting discoveries in the area of CQDs from both fundamental and practical standpoints so that the realization of their potential in the optoelectronic areas can be facilitated.